John Hick's Philosophy of World Religions - Byrne, Peter (Scottish journal of theology, 1982)
The most important intellectual problems facing modern Christianity stem from our awareness that Christianity is but one religion alongside many. John Hick's philosophy of world religions deserves attention because amongst English theologians he has been one of those most concerned to give a systematic answer to these problems.